RANCANG BANGUN SMART APPLICATIONS E-RESTAURANT MANAGEMENT SYSTEM MENGGUNAKAN FRAMEWORK CODEIGNITER - Sasmita Sasmita; Inda Anggraini (JITEK (Jurnal Ilmiah Teknosains), 2022)
This study aims to produce a smart application restaurant management system using a codeigniter framework. Problems that can be found at the Lesehan Ridwan shop when a customer wants to place an order, the employee must record the order through paper media and give the note to the kitchen for the cashier to perform calculations using a manual system too, such as using a calculator or using paper media without using computerized altogether, making it difficult for restaurant owners at Warung Alam Lesehan Ridwan to monitor and get sales reports for a certain period. Can make it easier and faster to help manage data at the restaurant. The system development method used in this research is the waterfall method. Smart applications e-restaurant are created using the PHP programming language with the Codeigniter framework. This system is expected to improve the management system of the restaurant. The research results obtained from the feasibility test for the design of smart applications e-restaurant management system using a codeigniter framework, the alpha test results obtained from the feasibility test of the system with an overall value of 3.6 by the expert stated that it was feasible and the results of testing betha obtained a value of 4.2 by the user stated worth using. So that smart applications e-restaurant can be implemented as a medium for ordering food.